Effects of In utero environment and maternal behavior on neuroendocrine and behavioral alterations in a mouse model of prenatal trauma. Issue 11 (9th March 2016) - Golub, Y.; Canneva, F.; Funke, R.; Frey, S.; Distler, J.; von Hörsten, S.; Freitag, C. M.; Kratz, O.; Moll, G. H.; Solati, J.
ABSTRACT: Maternal posttraumatic stress disorder (PTSD) following trauma exposure during pregnancy is associated with an increased risk of affective disorders in children. To investigate the mechanisms by which prenatal trauma and/or maternal PTSD affect brain development and behavior we established a mouse model of prenatal traumatic (PT) experience based on the application of an electric foot shock to C57Bl/6N female mice on the gestational day 12 during their pregnancy. The model is based on a previously validated animal model of PTSD. We found high anxiety levels and poor maternal care along with reduced serum prolactin and increased corticosterone levels in dams following maternal trauma (MT). PT‐pups were born smaller and stayed smaller throughout their life. We show increased time and frequency of ultrasonic calls in PT‐pups when separated from the mothers on the postnatal day (PND) 9. Cross‐fostering experiments reveal lower anxiety levels in PT pups raised by healthy mothers as compared to trauma‐naive pups raised by MT‐dams. Importantly, the combination of prenatal trauma and being raised by a traumatized mother leads to: (1) the highest corticosterone levels in pups, (2) longest USV‐call time and (3) highest anxiety levels in comparison to other experimental groups. Our data indicates a distinct change in maternal care following MT which is possibly associated with trauma‐induced decrease in prolactin levels. Furthermore, we show that maternal behavior is crucial for the development of the offspring anxiety and specific aspects in maternal care overwrite to a significant extend the effects of in utero and postnatal environment. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 76: 1254–1265, 2016